The parkable piezoprobe for determining cv and strength – modelling and interpretation methods. Issue 5 (18th June 2018) - Schneider, M. A.; Stanier, S. A.; Chatterjee, S.; White, D. J.; Randolph, M. F.
Abstract : The parkable piezoprobe is a site investigation tool for measuring the coefficient of consolidation, in situ offshore, at shallow embedment depths. The device applies a similar bearing pressure to subsea infrastructure so it reaches a comparable self-weight penetration when 'parked' at the seabed, representative of an unburied pipeline. Instrumentation on the device allows the dissipation of penetration-induced excess pore pressure to be recorded at various locations on the surface. From these dissipation responses the coefficient of consolidation can be inferred, which is a key parameter in the design of many offshore structures founded in surficial soil, such as pipelines or shallow foundations. The intent is that this device is deployed from a seabed frame, while other activities such as penetrometer testing or sampling take place in parallel. This paper presents robust interpretation methods for the parkable piezoprobe by using a combination of centrifuge experiments and large deformation finite-element analyses. The centrifuge tests demonstrate that the penetration response of the parkable piezoprobe is adequately captured by existing bearing capacity models, allowing the optimum device weight to be identified. A comprehensive interpretation method is then developed for the dissipation stage. This yields accurate estimates of the coefficient of consolidation, even for cases where there is no prior knowledge of the soil parameters or the depth to which the device embeds under its own self-weight.